On conditions of the solvability of nonlocal multi-point boundary value problems for quasi-linear systems of hyperbolic equations - Assanova, Anar Turmaganbetkyzy; Imanchiev, Askarbek Ermekovich (Eurasian Mathematical Journal, 2015)
A nonlocal multi-point boundary value problem for a system of quasi-linear hyperbolic equations is investigated. Based on the results for linear problems coefficient conditions are established ensuring the existence of classical solutions to nonlocal multi-point boundary value problem for a system of quasi-linear hyperbolic equations, and algorithms of finding these solutions are suggested.